Electron localizability indicators ELI-D and ELIA for highly correlated wavefunctions of homonuclear dimers. II. N2, O2, F2, and Ne2 - Bezugly, Viktor (Journal of computational chemistry, 2010)
Copyright 2010 Wiley Periodicals, Inc.